Rilla of Ingleside - Montgomery, L. M. (New York : Bantam Books, 1921)
Fifteen-year-old Rilla, the daughter of Anne Shirley Blythe, grows from a carefree, irresponsible girl into a strong and capable young woman during the war years, 1914-1918.
Keywords: World War, 1914-1918 -- Prince Edward Island -- Juvenile fiction; Prince Edward Island -- Fiction